Prevalence and its influencing risk factors of subclinical mastitis in crossbred Friesian cows (Bangladesh Veterinarian, 2018)
The prevalence and risk factors associated with subclinical mastitis in crossbred Friesian cows in selected dairy farms were studied using California Mastitis Test (CMT). A total of 287 cows and 1148 quarters were examined. Cow parity, age, body condition score (BCS), milk yield and lactation stage were collected by using pretested questionnaire. The prevalence of subclinical mastitis was 41.1%. Among tested cows, 15.8% showed moderate and 5.5% strong reaction to CMT (P